2009
DOI: 10.1590/s1807-59322009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Hospital Anxiety and Depression Scale (HADS) in a Cardiac Emergency Room – Chest Pain Unit

Abstract: OBJECTIVE: To determine the prevalence of anxiety and depression in patients complaining of chest pain who seek a chest pain unit attendance. INTRODUCTION: Patients arriving at a Chest Pain Unit may present psychiatric disorders not identified, isolated or co-morbid to the main illness, which may interfere in the patient prognosis. METHODOLOGY: Patients were assessed by the "Hospital Anxiety and Depression Scale" as a screening instrument wile following a systematized protocol to rule out the diagnosis of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…NCCP patients were found to have similar anxiety scores to CCP patients,26–28 but higher levels of anxiety than patients with a determined cause (be it cardiac or another disease such as pneumonia)30 and healthy controls 20 30. Likewise, the percentage of respondents scoring above predefined cut-off scores for probable anxiety was similar for NCCP and CCP patients,26 27 but higher among NCCP patients than those with a determined cause for their chest pain30 and healthy controls 20. The mean baseline anxiety scores for NCCP patients tended to be just below the cut-off for mild anxiety; nonetheless, between 21% and 53.5% of NCCP patients were categorised as probably having anxiety, although it should be noted that different cut-off scores were used across studies.…”
Section: Review Findingsmentioning
confidence: 92%
See 1 more Smart Citation
“…NCCP patients were found to have similar anxiety scores to CCP patients,26–28 but higher levels of anxiety than patients with a determined cause (be it cardiac or another disease such as pneumonia)30 and healthy controls 20 30. Likewise, the percentage of respondents scoring above predefined cut-off scores for probable anxiety was similar for NCCP and CCP patients,26 27 but higher among NCCP patients than those with a determined cause for their chest pain30 and healthy controls 20. The mean baseline anxiety scores for NCCP patients tended to be just below the cut-off for mild anxiety; nonetheless, between 21% and 53.5% of NCCP patients were categorised as probably having anxiety, although it should be noted that different cut-off scores were used across studies.…”
Section: Review Findingsmentioning
confidence: 92%
“…There was some variety in the procedures for excluding cardiac causes of chest pain. Most studies reported procedures similar to CPU care (ie, blood tests for cardiac enzymes, ECG, chest x-ray, exercise tolerance test) or equally thorough processes,22–27 30 whereas one study only reported using physical examination and ECG to rule out cardiac causes 29. Two studies did not provide sufficient information on the testing procedures 20 28.…”
Section: Review Findingsmentioning
confidence: 99%
“…More than half of the patients consulting the emergency department due to chest pain are diagnosed with non-cardiac chest pain (NCCP) or unexplained chest pain. 2,[7][8][9][10][11][12] Non-cardiac chest pain is defined as angina-like pain with no evidence of ischemic heart disease (IHD) 2,8 and unexplained chest pain as pain that has not been explained by any obvious organic cause. 13 While there are well established guidelines for diagnosing and treating patients with IHD, [14][15][16] an international consensus approach to treat patients with NCCP is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Of these studies, that by Almeida (1999) was excluded because it assessed patients with dementia, seven studies were excluded because they assessed community-based elderly individuals, [10][11][12][13][14][15][16] and five were excluded because they did not report prevalence rates among the elderly. [17][18][19][20][21] Six studies that assessed samples comprising less than 100 individuals [22][23][24][25][26][27] were retained. In the study conducted by Porcu et al, 24 elderly subjects were investigated in hospitals and LTCFs and the respective prevalence rates reported separately.…”
Section: Resultsmentioning
confidence: 99%